Factors Related to Nutritional Status of Pregnant Women in the Working Area of Baiturrahman Health Center Banda Aceh (Unnes Journal of Public Health, 2019)
According to the 2012 Indonesian demographic and health survey (IDHS), in PRAKARSA Policy Maternal mortality rate update of 359 per 100.000 live births. Nutritional problems that are often faced by pregnant women are Chronic Energy Deficiency (CED) and nutritional anemia. According to the Indonesian Ministry of Health in 2013, the prevalence of CED pregnant women was 24.2%. This was a survey research with descriptive analytical and cross sectional design. The sample in this study were 80 people. Analysis of data in the form of univariate, bivariate and multivariate. The results showed that Knowledge (p = 0.015, PR = 4.608), Attitude (p = 0.008, PR = 7.933), Family Support (p = 0.035, PR = 3.857), Family income level (p = 0.009, PR = 5,000) , parity (p = 0.003, PR = 6,667), sexual relations behaviour (p = 0.598). The results of the dominant variable multivariate analysis were attitudes obtained. The most dominant variable related to nutritional status of pregnant women was PR = 8,576. It can be concluded that there is a relationship knowledge, attitudes and family support with nutritional status of pregnant women while family income level is not a related factor Attitude variables are dominant factors at risk of developing CED.